Learn Number Lines with Interactive Video Learning Media - I Komang Aditya Sadewa; I Ketut Dibia; Ndara Tanggu Renda (Universitas Pendidikan Ganesha, 2022)
This research is motivated by the difficulties of the teacher in implementing online learning, which makes students less enthusiastic and less able to understand the material in online learning, so the development of interactive video media is needed. This study aims to produce interactive video media for grade three elementary school number line materials tested for validity. The development model used in this study is the ADDIE model. The subjects in this study consisted of 1 teacher and four dose experts who were experts in their fields as media experts and material experts, and 12 students consisting of 3 people as individual tests and nine students as small group tests. The method of data collection in this study is the method of questionnaires and interviews. The data generated in this study are qualitative and quantitative. The data obtained were then analyzed using the mean formula to determine the average validation of interactive video media. The development of interactive video media was declared valid based on the assessments of media experts, design experts, material experts, individual test students, and small group students with an average range of 4.01 < X 5, with the qualification